Effect of Some Chemical Factors on Pullulan Production from Date Syrup by Alocal Isolate of the Fungus Aurobisedium Pullulans - Haidar, Mustafa M.; Adil, Jeen N. (Science Journal of University of Zakho, 2017)
This study was developed to use Iraqi date syrup as a carbon source and basal substrate for the production of the exopolysaccharide “Pullulan” by the yeast like fungus A. pullulans. It has been revealed that the best incubation period for high accumulation of pullulan was three days of incubation with initial pH value of 6.5. Also, the fermentation medium of 12% sugar was found to be superior to other sugar concentrations with respect to pullulan production. Moreover, the results of the addition of different nitrogen source containing same amounts of nitrogen present in 0.2% ammonium sulphate show that the urea stimulated pullulan biosynthesis by the fungus more than other tested nitrogen sources. Additionally, highest production of pullulan was obtained when a concentration of 0.2% sodium chloride and was added to the fermentation medium.